Main conceptual provisions of the creation of an electronic state register of immovable cultural heritage of Ukraine. Part 2: processes - V. Chabaniuk; O. Dyshlyk; K. Polyvach; V. Pioro; I. Kolimasov; J. Nechyporenko (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2022)
Abstract. Part 2 describes the processes of activities for the creation of a new modern electronic State Register of Immovable Cultural Heritage (CH) of Ukraine. They are part of the methodology based on AGIS-CH1 Solutions Framework (SoFr), where AGIS-CH1 represents the first queue of the hierarchically structured Atlas GeoInformation System (AGIS). AGIS-CH generally consists of four strata: Operational (w), Application (a), Conceptual (b) and General (g). The processes in the article refer to AGIS1 aSoFr, which determines the activities "between" AGIS1 subsystems of the Application and Operational strata. The processes related to bSoFr AGIS-CH1, which determines the activities "between" AGIS-CH1 subsystems of the Conceptual and Application strata, are also mentioned.